2021
DOI: 10.1111/sum.12782
|View full text |Cite
|
Sign up to set email alerts
|

Base cation‐enhancing role of corn straw biochar in an acidic soil

Abstract: Biochar affects base cation retention and leaching when it is used to enhance the base cation status of acidic soil. However, the details of its contribution are not yet clear. In this study, six loadings of corn straw biochar (0%, 2%, 4%, 6%, 8% and 10%, w/w) were applied to an acidic Ferralsol and incubated for 1 year. The results showed that the content of water‐soluble and exchangeable base cations of K, Na, Ca and Mg increased with increasing levels of biochar in amended soil. The percentage of water‐solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The reduced ESP in incubated soils with moderate/light salinization (Table 2, group B and group C) could be attributed to a remarkable increase in Ca 2+ and Mg 2+ . Previous studies have revealed that biochar could be employed for supplying Ca 2+ /Mg 2+ in acidic soil [30]. However, total Ca/Mg content in SMSHC was insufficient to meet the increased concentration of exchangeable Ca 2+ /Mg 2+ , especially in C6 (Table 1 vs. Table 3).…”
Section: Esp and Exchangeable Na + Ca 2+ Mg 2+mentioning
confidence: 98%
See 1 more Smart Citation
“…The reduced ESP in incubated soils with moderate/light salinization (Table 2, group B and group C) could be attributed to a remarkable increase in Ca 2+ and Mg 2+ . Previous studies have revealed that biochar could be employed for supplying Ca 2+ /Mg 2+ in acidic soil [30]. However, total Ca/Mg content in SMSHC was insufficient to meet the increased concentration of exchangeable Ca 2+ /Mg 2+ , especially in C6 (Table 1 vs. Table 3).…”
Section: Esp and Exchangeable Na + Ca 2+ Mg 2+mentioning
confidence: 98%
“…It may be due to a low-temperature hydrothermal reaction that provides charring products with a more humid, acid-like structure on the surface of SMSHC [32]. In the context of the low available P content, SMSHC improved soil P availability probably by dissolving phosphate crystal phases [30]. A possible explanation for the poor improvement of available P in light saline-sodic soil (Figure 2B) could be due to the negative effect of Ca 2+ on P availability.…”
Section: Soil Nutrientsmentioning
confidence: 99%